Enhancing Vietnamese Vocabulary Knowledge and Vietnamese Listening Ability through the Total Physical Response Method of Grade 1 Students Satit School Under Rajabhat University, Thailand - Thanh, Nguyen Thi Thu; Pichayakul, Thitiporn; Klangphahol, Kanreutai (VNU Journal of Science: Education Research; Vol 36 No 2DO - 10.25073/2588-1159/vnuer.4377, 2020)
The purpose of this research was 1) to enhance Vietnamese vocabulary knowledge through the Total Physical Response (TPR) 2) to enhance Vietnamese Listening abilities through the Total Physical Response (TPR). The scope of the study is grade 1 students in the second semester, academic year 2019, at The Demonstration School of Valaya Alongkorn Rajabhat University Under The Royal Patronage satit by Purposive Sampling. The instruments used in this research were consisted of 1) lesson plans 2) Vietnamese vocabulary test 3) Vietnamese listening comprehension test. The statistics used to analyze the data were mean, percentage and standard deviation and t-test dependent. The result of this study indicated that Vietnamese vocabulary knowledge and Vietnamese listening ability of the students increased after learning through the Total Physical Response.